2014
DOI: 10.1177/0003489414546605
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings in Children With Tinnitus

Abstract: Magnetic resonance imaging would appear to be mandatory in the investigation of tinnitus in children who are found to have sensorineural hearing loss, particularly to rule out the diagnosis of multiple sclerosis. Although our study does not support the routine use of MRI in children with normal audiology, the numbers in our series are too small for a conclusive recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Of those patients with imaging data, they underwent imaging for reasons other than their tinnitus, and the majority (69.4%) of these children also had normal results. Levi et al 26 found that 4 out of 9 children with tinnitus who had abnormal audiograms also had abnormal MRI results; 3 of those 4 were diagnosed with multiple sclerosis. These findings suggest that MRI may have a role in the workup of children with abnormal hearing and tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Of those patients with imaging data, they underwent imaging for reasons other than their tinnitus, and the majority (69.4%) of these children also had normal results. Levi et al 26 found that 4 out of 9 children with tinnitus who had abnormal audiograms also had abnormal MRI results; 3 of those 4 were diagnosed with multiple sclerosis. These findings suggest that MRI may have a role in the workup of children with abnormal hearing and tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…However, pediatric tinnitus needs to be reviewed in a similarly rigorous manner when there is sufficient research or publications in the areas examined by the guideline. As such, Levi et al made a recommendation in imaging children with tinnitus that deserves comment. In their series of nine children, four children with concomitant tinnitus and SNHL underwent MRI; all were abnormal, and three were found to have multiple sclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…As such, Levi et al made a recommendation in imaging children with tinnitus that deserves comment. In their series of nine children, four children with concomitant tinnitus and SNHL underwent MRI; all were abnormal, and three were found to have multiple sclerosis . The authors went on to conclude that MRI is mandatory for those with abnormal audiograms.…”
Section: Discussionmentioning
confidence: 99%
“…Newer sequences, such as diffusion weighted, as well as further development of high-energy MRI, have allowed for higher resolution and further characterization of lesions (3,6,(8)(9)(10). MRI studies have been a valuable tool for follow-up of cholesteatoma in children, but there is currently growing evidence for a role of this imaging modality in evaluating other otologic complaints in the pediatric population, particularly for diagnostic value of intracranial pathology (11)(12)(13)(14).…”
mentioning
confidence: 99%